1987
DOI: 10.2190/0uq0-wv6p-2r6v-2qdq
|View full text |Cite
|
Sign up to set email alerts
|

Gender Hierarchies in the Health Labor Force

Abstract: Rapid growth and increasing diversity characterize trends of the U.S. health labor force in recent decades. While these trends have promoted change on many different fronts of the health system, hierarchical organization of the health work force remains intact. Workers continue to be stratified by class and race. Superimposed on both strata is a structure that segregates jobs by gender, between and within health occupations. While female health workers outnumber males by three to one, they remain clustered in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
0
1

Year Published

1988
1988
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 10 publications
4
14
0
1
Order By: Relevance
“…This seems to suggest that many females who occupy managerial positions are there by virtue of their greater numbers in the profession, as opposed to any need to realize their values through administrative roles. Research on therapists in the United States supports a trend towards an increasing number of males in higher-salaried leadership positions, which is consistent with other health care positions in the United States (Butter, Carpenter, Kay, & Simmons, 1987). …”
Section: Discussionsupporting
confidence: 76%
“…This seems to suggest that many females who occupy managerial positions are there by virtue of their greater numbers in the profession, as opposed to any need to realize their values through administrative roles. Research on therapists in the United States supports a trend towards an increasing number of males in higher-salaried leadership positions, which is consistent with other health care positions in the United States (Butter, Carpenter, Kay, & Simmons, 1987). …”
Section: Discussionsupporting
confidence: 76%
“…Men in female-dominated health professions Authors of nursing and social work literature have made many attempts to address the topic of males within female-dominated health professions (Butter et al, 1987;Egeland & Brown, 1989;Kadushin, 1976;Wharton & Baron, 1987). Kadushin (1976) suggested that there are considerable advantages to being in any profession in which males are a minority.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In other studies, men have indicated salary levels as the primary source of job dissatisfaction and some have even suggested that the large proportion of females in their professions is the cause of low salaries (Butter et al, 1987;Rider & Brashear, 1988;Wharton & Baron, 1987). Nonetheless, men have been adapting to the difficulties they have encountered within these professions by specializing in areas that they perceive to be more congruent with traditional male roles (Egeland & Brown, 1989;Kadushin, 1976).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…This case also differs from other studies on the feminization of employment (e.g., Coventry 1999;Muzzin et al 1994;Reskin and Roos 1990) in that many women enter PA work because it offers an alternative to traditional nursing careers and the demanding schedules of physicians. This is salient because women are normally segregated into lower status work and encounter barriers when entering higher status professions (Butter et al 1994). Being a PA allows women to practice medicine, albeit under supervision, while simultaneously balancing their family life.…”
Section: Introductionmentioning
confidence: 99%